Evaluation and detection of Brassicaceae leafy whey phytohormones efficacy for exploiting as a medium obtaining optimistic culture of fungi in vitro - Rajesh Jadhav (Innovations in Agriculture, 2019)
The DPJ (Deproteinised Juice) or whey constituents were responsible for the induction of growth optimization of plants, various fungi including yeast, Rhizobium reported by earlier workers. In previous experiments, DPJ maximised the growth of plants and seed germination. During present investigation the carbohydrates, amino acids and protein tests were taken into the consideration. All the tests found positive. Despite, the extract is deproteinised, still there was persistence of few proteins and amino acids. The collection of mycelia grown on DPJ was filtered and the culture filtrates recommended to use in vitro for the industrial purpose for biomass and secondary metabolites. Experimental DPJ is compared with the glucose nitrate medium as control. These positive tests revealed the suitability of DPJ to be used as the medium for the growth of fungi. Positive amino acid tests conspicuously revealed presence of phytohormones in members of Brassicaceae DPJ and hence advisable to be utilised for the plant growth in vivo, plant callus growth and cell proliferation of mycelia in vitro.